Using the Wesleyan Quadrilateral to Teach Biblical Studies in Christian Liberal Arts Colleges - Cosby, Michael R. (Teaching theology and religion, 2001)
Biblical studies professors in Christian liberal arts colleges typically face greater hostility from students nurtured in fundamentalist churches than they do from those who attend mainline churches. Guiding them through their first academic study of the Bible poses many challenges. To avoid the course becoming a battlefield, and to facilitate integration on a higher level, the Wesleyan Quadrilateral provides a middle way between right-wing and left-wing extremes. This approach gives priority to the Bible as the primary source for determining theology and practice, but relies heavily on tradition, reason, and experience as well. It also promotes interaction with the spiritual, moral, and ethical concerns expressed in the biblical texts. To adopt the Quadrilateral involves active concern for character formation, inspiring students to become better people. If we merely dispense historical-critical or literary information without considering contemporary relevance, we bore students and fail in our duties as educators.